2015
DOI: 10.1521/aeap.2015.27.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Informing the Scaling Up of Voluntary Medical Male Circumcision Efforts Through the Use of Theory of Reasoned Action: Survey Findings Among Uncircumcised Young Men in Swaziland

Abstract: Assessing predictors of intention to circumcise can help to identify effective strategies for increasing uptake of voluntary medical male circumcision (VMMC). Grounded in the theory of reasoned action (TRA), the current study of uncircumcised males ages 13-29 in Swaziland (N = 1,257) employed multivariate logistic regression to determine predictors of VMMC intention. The strongest predictors were strongly disagreeing/disagreeing that sex was more painful for a circumcised man (odds ratio [OR] = 4.37; p = < .00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The ndings of this study indicated the circumcision prevalence (48.98%) was higher in this study than the recent global estimation of male circumcision which is at 37-39%, where almost half of these procedures are carried out for cultural or religious reasons (25,26). EmaSwati do not circumcise in the cultural context and some common myths including the foreskin making a certain spice, reduction of libido and the operation being very painful (27). The prevalence on this study is slightly higher than a self-reported prevalence of 42.8% done in South Africa (28).…”
Section: Discussionmentioning
confidence: 50%
“…The ndings of this study indicated the circumcision prevalence (48.98%) was higher in this study than the recent global estimation of male circumcision which is at 37-39%, where almost half of these procedures are carried out for cultural or religious reasons (25,26). EmaSwati do not circumcise in the cultural context and some common myths including the foreskin making a certain spice, reduction of libido and the operation being very painful (27). The prevalence on this study is slightly higher than a self-reported prevalence of 42.8% done in South Africa (28).…”
Section: Discussionmentioning
confidence: 50%
“…No studies have assessed perceived descriptive norms about male circumcision uptake in Uganda. Young uncircumcised men in eSwatini were more likely to report a personal intention to get circumcised if they thought that their friends, parents, or partner encouraged male circumcision and if they thought that most male friends were circumcised [72]. Similarly, young uncircumcised men in Zimbabwe were more likely to report a personal intention to get circumcised if they believed that their mother would encourage male circumcision and if they believed that male friends would get circumcised [73].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In Mozambique, data from population-based surveys have contributed to estimating the prevalence of male circumcision among men, which assists in assessing if the target coverage of VMMC is being met. [9]. However, more information is necessary for determining the relative preventive benefits of traditional male circumcision in addition to MMC in preventing HIV infection.…”
Section: Introductionmentioning
confidence: 99%